HLA-DR-DQ haplotypes and type 1 diabetes in Macedonia - Ilonen, Jorma; Kocova, Mirjana; Lipponen, Kati; Sukarova-Angelovska, Elena; Jovanovska, Aleksandra; Knip, Mikael (Elsevier BV, 2009)
The lowest incidence of childhood type 1 diabetes in Europe has been reported from the Republic of Macedonia. To assess the possible genetic contribution we analyzed the distribution of HLA-DR-DQ haplotypes among 163 diabetic children and 239 healthy controls. Similar disease associations were found as in other Caucasian populations. HLA-(DR3)-DQA1*05-DQB1*02 was the most common disease associated haplotype, but several DRB1*04-DQB1*0302 haplotypes were also found increased among patients. DRB1*0402 was the most common DR4 allele among them. The high frequency of protective (DR11/12)-DQA1*05-DQB1*0301 and (DR14)-DQB1*0503 haplotypes as well as of neutral (DR1/10)-DQB1*0501 and (DR16)-DQB1*0502 haplotypes were characteristic for the background population. Although a relatively low frequency of predisposing and a high frequency of protective haplotypes was detected, the haplotype frequency distribution did not markedly differ from that reported from other Eastern Mediterranean populations and these differences cannot be the sole explanation for the low disease incidence in Macedonia.